Exports, Export Destinations, and Skills - Brambilla, Irene; Lederman, Daniel; Porto, Guido (American Economic Review, 2012)
This paper explores the links between exports, export destinations, and skill utilization. We identify two mechanisms behind these links: differences across destinations in quality valuation and in exporting required services, activities that are intensive in skilled labor. Depending on the characteristics of the source country (income, language), the theories suggest a skill-bias in export destinations. We test the theory using a panel of Argentine manufacturing firms. We find that Argentine firms exporting to high-income countries hired more skilled workers than other exporters and domestic firms. Instead, we cannot identify any causal effect of exporting per se on skill utilization. (JEL F14, F16, J24, L60, O14, O19)